SKILL EDITING EXAMINATION STUDENTS OF PUBLISHING STUDIES STATE POLYTECHNICS OF CREATIVE MEDIA - Erlan Saefuddin (Jurnal Ilmiah Publipreneur, 2020)
This paper examines the problem of low editing skills , especially among students of Creative Media State Polytechnic Publishing. This study also departs from the problem of untested editing skills . Therefore, this article aims to 1) map the level of testing of the editing skills of the Creative Media State Polytechnic Publishing Study Program Students with a specialization in editing; 2) mapping the level of editing skill testing of the State Polytechnic Creative Media Publishing Study Program Students with a specialization in writing; 3) produce a comparison map of the testing skills of the State Polytechnic Creative Media Publishing Study Program between those who are interested in editing with those who are interested in writing. The study with the grand qualitative method used a script editing design. The data processing methods are descriptive and comparative. The data collection techniques applied were interviews and questionnaires. The activity plan showing the procedure for this study is as follows. Publishing student data collection who will be the study sample. Conducting interviews to get initial data. Testing the editing competence of Publishing students. Processing test data. Formulating policies, models, and conclusions.This study has resulted in the editing competency level of the Creative Media State Polytechnic Publishing students. The level of competence does not represent a qualified ability. The basic editing skills of the tested students showed a very good level as evidenced by their generally very good grades. Spelling and grammar skills are quite good. However, the syntactic capabilities still need to be improved. Therefore, the improvement of editing competency still needs to be improved, especially with regard to applied editing. According to the level achievement of the editing competency level of the Creative Media State Polytechnic Publishing student, the following conclusions can be generated. Editing education process is not based on the knowledge aspect, but prioritizes practice. Language problems are an element that must be strengthened in Creative Media State Polytechnic Publishing Students. Elements of spelling, words, and sentences are a matter of editing that must be further honed.